2023
DOI: 10.1038/s41422-023-00826-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel N6-Deoxyadenine methyltransferase METL-9 modulates C. elegans immunity via dichotomous mechanisms

Abstract: N6-Methyldeoxyadenine (6mA) has been rediscovered as a DNA modification with potential biological function in metazoans. However, the physiological function and regulatory mechanisms regarding the establishment, maintenance and removal of 6mA in eukaryotes are still poorly understood. Here we show that genomic 6mA levels change in response to pathogenic infection in Caenorhabditis elegans (C. elegans). We further identify METL-9 as the methyltransferase that catalyzes DNA 6mA modifications upon pathogen infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The study by Ma et al 6 in Cell Research reported that 6mA levels in C. elegans gDNA increased greatly when the animals were infected by bacteria (Fig. 1).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The study by Ma et al 6 in Cell Research reported that 6mA levels in C. elegans gDNA increased greatly when the animals were infected by bacteria (Fig. 1).…”
mentioning
confidence: 86%
“…N 6 -methyldeoxyadenosine (6mA) is well characterized as the most abundant DNA modification in many prokaryotes, regulating fundamental processes such as DNA transcription, replication, and repair. 1 Since 2015, high levels of 6mA were detected in the genomes of several lower eukaryotes with unique distribution patterns, suggesting regulatory roles of 6mA as an additional DNA mark in these systems.…”
mentioning
confidence: 99%
“…Caenorhabditis elegans ( C. elegans ), characterized by its small size, short lifecycle, transparent body, suitability for large-scale genetic research and phenotype analysis, and sensitivity to various environmental exposures, has proven to be a robust invertebrate model for investigating host-pathogen interactions ( Martineau et al, 2021 ; Qu et al, 2023a ; Ma et al, 2023 ). Like other invertebrates, C. elegans relies entirely on its innate immune system to defend against pathogens.…”
Section: Introductionmentioning
confidence: 99%